The Effect of Fixed-Term Employment on Well-Being: Disentangling the Micro-Mechanisms and the Moderating Role of Social Cohesion - Sonja Scheuring (Social Indicators Research, 2020)
This paper examines the impact of fixed-term employment on well-being from a cross-national comparative perspective by testing (1) the effect heterogeneity across European countries, (2) to which extent Jahoda's Latent Deprivation Model provides a sufficient micro-level explanation for the underlying mechanisms and (3) whether the macro-level factor of social cohesion weakens the micro-level impacts. We investigate the effects in both an upwards (permanent employment) and a downwards (unemployment) comparative control group design. Due to the mediating role of social contacts on the micro-level, we assume social cohesion on the country-level to moderate the main effects: A high degree of societal affiliation should substitute the function of social contacts in the work environment of individuals. Using microdata from the European Social Survey (ESS) 2012 for 23 countries and applying multilevel estimation procedures, we find that there is a remarkable variation in the effects across countries. Even though in each country fixed-term employees have a lower subjective well-being compared to permanent ones, the point estimates vary from .17 to 1.19 units. When comparing fixed-term employees to unemployed individuals, the coefficients even range from -0.167em.27 to 1.25 units. More specifically, a negative effect indicates that having a fixed-term contract is worse than unemployment in some countries. Moreover, pooled linear regression models reveal that Jahoda's Latent Deprivation Model explains about three-quarters of the micro-level effect sizes for both directions. Eventually, social cohesion on the country-level diminishes the individual-level well-being differences between fixed-term employees and permanent individuals but not between fixed-term employees and the unemployed.
Keywords: 300; Fixed-term employment; Well-being; Social cohesion; Multilevel estimation; Mediation analysis